Construction of mechanically robust superamphiphobic surfaces on fiber using large particles - LV, Chang; WANG, Jinyi; TIAN, Qirong; ZHANG, Zhicheng; WANG, Tao; LIU, Rongfei; WANG, Sheng (Frontiers of materials science, 2022)
Superamphiphobic surfaces have attracted the attention of researchers because of their broad application prospects. Currently, superamphiphobicity is primarily achieved by minimizing the solid–liquid contact area. Over the past few decades, researchers have primarily focused on using physical deposition methods to construct superamphiphobic surfaces using fine-sized nanoparticles (< 100 nm). However, porous hollow SiO 2 particles (PH-SiO 2), which are typically large spheres, have a highly hierarchical structure and can provide lower solid–liquid contact fractions than those provided by fine-sized particles. In this study, we used PH-SiO 2 as building blocks and combined them with poly (dimethylsiloxane) to construct a mechanically robust coating on fiber by spray-coating. After chemical vapor deposition treatment, the coating exhibited excellent superamphiphobicity and could repel various liquids, covering a wide range of surface tensions (27.4–72.0 mN·m −1).